Indium Gallium Nitride Based Light Emitting Diode Using Pre-Roughened Backside (N-Face) Gallium Nitride Substrate - Alias, Ezzah Azimah (2024)
This project attempts to improve the performance of InGaN LEDs grown on GaN substrates. To achieve this goal, three frameworks were proposed. Firstly, by introducing GaN cap layer in multiquantum wells (MQWs). Secondly, by roughening backside (N-face) of GaN substrate using new etching solution and annealing the substrate before roughening. Thirdly, by roughening GaN substrate prior to LED growth.